2023
DOI: 10.1038/s41564-022-01319-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive nanobacteria with host-dependent traits pervade Omnitrophota

Abstract: Candidate bacterial phylum Omnitrophota has not been isolated and is poorly understood. We analysed 72 newly sequenced and 349 existing Omnitrophota genomes representing 6 classes and 276 species, along with Earth Microbiome Project data to evaluate habitat, metabolic traits and lifestyles. We applied fluorescence-activated cell sorting and differential size filtration, and showed that most Omnitrophota are ultra-small (~0.2 μm) cells that are found in water, sediments and soils. Omnitrophota genomes in 6 clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Omnitrophota in a recent metagenomic study, in which most Ca . Omnitrophota bacteria are predators and parasites ( Perez-Molphe-Montoya et al., 2022 ; Seymour et al., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Omnitrophota in a recent metagenomic study, in which most Ca . Omnitrophota bacteria are predators and parasites ( Perez-Molphe-Montoya et al., 2022 ; Seymour et al., 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…V. archaevorus LiM and Ca. Omnitrophica bacterium OLB16, encoding SpeDC enzymes investigated in the current study, biosynthetic pathways for PLP are missing or incomplete across the phylum ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microsyncoccus PMX.50 (Tables S2 and S4), which are encoded by type IV pilus assembly proteins (Table S2). In a previous study, ATPase and type IV pili were predicted to function in attachment and motility on larger host surfaces ( 18 ). Furthermore, some active peptidase-like proteins with signal peptides (PMX_810_sub_00385, PMX_810_sub_00508, PMX.108_00125, PMX.108_00310, PMX.108_00457, PMX.108_00476, and PMX.50_00413) (Table S2) and substrate-binding proteins of amino acid/metal transport systems were found in the three Ca .…”
Section: Observationmentioning
confidence: 98%
“…Previous studies have suggested that the competence protein ComEC, secretion systems, pilus, and several transporters are important for the parasitism or predatory lifestyles of ultrasmall microbes, including Ca . Patescibacteria ( 15 18 ). Accordingly, these genes were highly expressed in the genome of Ca .…”
Section: Observationmentioning
confidence: 99%